Risks of Endometrial Carcinogenesis and Assisted Reproductive Technologies: A Systematic Review and Meta-Analysis (London Journal of Medical and Health Research, 2024)
Purpose of study: to study the possible relationship between in vitro fertilization, the use of ovulation stimulation drugs and the risk of developing uterine cancer in women with infertility.Material and methods: literature search for a systematic review was carried out in the bibliographic databases Medline, ClinicalKey, Google Scholar, Embase, The Cochrane Library, eLIBRARY for the period 1999-2022. Publications were searched using keywords defined according to the PICO principle (P = population or patients, I = intervention, C = comparison and O = outcomes): female, women, infertility, infertility treatment, in vitro fertilization, IVF, assisted reproductive technologies, ART, ovarian stimulation, ovarian hyperstimulation, clomiphene citrate, hCG, hMG, tamoxifen, uterine, endometrial, cancer, carcinoma neoplasm, uterine neoplasms. The following SQL operators were used during the search: AND, OR.Results: As a result of the search, 37 representative publications were found, during the selection process 8 studies were selected for meta-analysis.Conclusion: A systematic review and meta-analysis has demonstrated the ambiguity of the design and results of studies on the possible relationship of uterine cancer and methods of assisted reproductive technologies published to date. The problem is very relevant due to the high incidence of infertility and the increase in the incidence of cancer of the female reproductive organs. The conducted studies confirm the impossibility to evaluate in isolation the carcinogenic effect of ovulation inducers or in vitro fertilization methods without adjusting for the infertility factor, as well as risk factors for uterine cancer. There remains a high need for more research as well as for the safety profile of infertility treatments in relation to long-term cancer risks.
Keywords: Social integration; responsibilities; relationships and mentorship; Metastasis.; resistance; Genomics; sequencing; prosigna; transduction.; In Vitro Fertilization; Meta-Analysis; uterine cancer; infertility; ovulation induction